Design Procedure and Simplified Equations for the Flexural Capacity of Concrete Members Reinforced with Fibre-reinforced Polymer Bars - Torres, Lluís; Neocleous, Kyriacos; Pilakoutas, Kypros (My University, 2012)
The predominant failure mode of concrete members reinforced with fibre-reinforced polymer (FRP) bars is flexural, due to either concrete crushing or FRP rupture. Many design tools have been developed for the flexural design of FRP-reinforced concrete. These tools are sufficiently accurate, but an iterative procedure is required when dealing with flexural failure due to FRP rupture. In addition, despite the fact that the design concepts involved are similar to those used for conventional steel-reinforced concrete, the changes in the design philosophy and the linear behaviour up to rupture of the FRP bars lead to the sectional properties having a different influence on the design, which not everyone may be familiar with. Therefore, this study proposes a general methodology for evaluating the design flexural capacity of FRP-reinforced concrete sections. This methodology is based on the design provisions of Eurocode 2 and comprises non-dimensional, closed-form equations, derived independently of the concrete and FRP characteristics. The proposed methodology can be used to derive universal dimensionless design charts as well as tables. The accuracy of the proposed design tools has been verified by comparing the predictions with the experimental results of 98 beams, which are available in the published literature. Copyright © 2012 Ernst & Sohn Verlag für Architektur und technische Wissenschaften GmbH & Co. KG, Berlin.
Keywords: Concrete crushing; Design; Flexural capacity; FRP bars; FRP rupture; Reinforced concrete